Indium phosphide quantum dot-bismuth tungstate composite material and preparation method and application thereof
By developing the indium phosphide quantum dot-bismuth tungstate composite material, the problem of existing photocatalysts requiring sacrificial agents when producing H2O2 is solved, and high-efficiency photocatalytic generation of H2O2 is achieved, and significant degradation effect is shown in the treatment of coking wastewater.
Patent Information
- Application Number
- CN202411904064.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing photocatalysts require the use of sacrificial agents when producing hydrogen peroxide (H2O2), which increases production costs, and the small size of quantum dots leads to difficulty in separation and recycling, low charge separation efficiency, and cannot meet practical application requirements.
A indium phosphide quantum dot-bismuth tungstate composite material was developed, and the composite material was synthesized through a specific preparation method, and the function of photocatalyzing H2O2 production was used to degrade coking wastewater treatment.
Without the use of sacrificial agents, the composite material exhibits efficient photocatalytic generation of H2O2 in pure water, with a yield of 17.45 mmol·g-1·h-1, which is significantly higher than the yield of pure InP and pure Bi2WO6, and can effectively degrade the chemical oxygen demand (COD) in coking wastewater.
Smart Images

Figure CN119702021A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to an indium phosphide quantum dot-bismuth tungstate composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is a clean energy source that decomposes into water and oxygen, making it an environmentally friendly option for various applications, including bleaching, green chemical synthesis, and wastewater treatment. Photocatalytic synthesis of H2O2 from O2 and H2O is an economical, clean, and green method with the potential for a wide range of applications. However, most photocatalysts reported to date require sacrificial agents (ethanol or methanol) to quench H2O2. + and promote the reduction of O2 to H2O2. This requirement increases the cost of H2O2 production and hinders the development of photocatalytic technology. Therefore, it is crucial to develop new and environmentally friendly H2O2 production methods.
[0003] Quantum dots (QDs), which are only a few nanometers in size in all three dimensions, have attracted great interest as exceptional semiconductor photocatalysts due to their unique physical properties. Various QDs, such as ZnS QDs, carbon QDs, and CdSe QDs, have been identified as efficient photocatalysts for H2O2 production. For example, the H2O2 yield of ZnS QDs and carbon QDs heterostructured nanofibers reached 2.89 mmol g without the use of sacrificial agents. -1 ·h -1 , with significant photocatalytic activity. However, the small size of quantum dots makes it difficult to separate and recycle the photocatalyst. At the same time, due to the low charge separation efficiency, its performance still cannot meet the requirements of practical applications. Therefore, it is crucial to propose new systems to improve the efficiency and stability of charge separation. Indium phosphide (InP) quantum dots are a promising alternative for directly converting solar energy into fuels, which are ideal for environmental and biological applications. However, although InP quantum dots have been used in the research of photoelectrodes and solar cells, their photocatalytic properties have rarely been studied. To the best of our knowledge, the production of H2O2 by a photocatalytic system based on InP quantum dots without the addition of sacrificial agents has not yet been reported.
[0004] In recent years, bismuth tungstate (Bi2WO6) has been widely used in the field of photocatalysis as an excellent visible light photocatalyst due to its high visible light activity, suitable band gap (2.8 eV) and layered tungsten oxide structure. As an excellent semiconductor, Bi2WO6 has become a hot topic in photocatalysis research due to its stable crystal structure, high quantum efficiency and excellent energy utilization ability. However, Bi2WO6 has some disadvantages, such as limited surface defects and rapid recombination of photogenerated carriers, which limit its photocatalytic performance. In order to overcome these challenges, a lot of efforts have been made, such as nanostructure modification, surface engineering and heterojunction / homojunction design. In recent years, the use of quantum dots to modify Bi2WO6 to enhance its photocatalytic activity has received extensive attention. In recent years, the use of quantum dots to modify Bi2WO6 to enhance its photocatalytic activity has received extensive attention. For example, Bi2WO6 / Cu2O QDs composites have been shown to improve the photocatalytic performance in the visible light range. In addition, Zn2SnO4 QDs-modified Bi2WO6 nanocomposites were prepared to improve the photocatalytic degradation efficiency of acetone. On this basis, the researchers successfully synthesized Bi2WO6 / CdS QDs composites and tested their photocatalytic activity by degrading rhodamine B (RhB) and tetracycline hydrochloride (TC) and reducing Cr(VI) in aqueous solution. However, to the best of our knowledge, the application of QDs-modified Bi2WO6 in photocatalytic production of H2O2 has not been reported. This unexplored new material provides a promising avenue for future research. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an indium phosphide quantum dot-bismuth tungstate composite material and its preparation method and application. The composite material has the function of photocatalytic production of H2O2 and has great application value in the degradation of coking wastewater treatment.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing an indium phosphide quantum dot-bismuth tungstate composite material is provided, comprising the following steps:
[0007] (1) adding an indium precursor to oleylamine and mixing, then gradually heating to 110-130° C. under nitrogen protection, keeping the temperature for a period of time, then heating to 170-190° C., and then adding tri(diphenylphosphine) to react to obtain indium phosphide quantum dots;
[0008] (2) dispersing bismuth nitrate in deionized water, adding hexadecyltrimethylammonium bromide and sodium tungstate in sequence and stirring evenly, and then performing a hydrothermal reaction to obtain bismuth tungstate microflowers;
[0009] (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) into deionized water and mixing them evenly, then heating for reaction, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0010] Furthermore, in step (1), the indium precursor is indium chloride.
[0011] Furthermore, in step (1), the molar volume ratio of the indium precursor, oleylamine and tri(diphenylphosphine) is 0.2-0.3 mmol:10 mL:0.5 mL.
[0012] Furthermore, in step (1), the temperature is kept at 50-70 minutes and the reaction is carried out for 20-40 minutes.
[0013] Furthermore, in step (2), the usage ratio of bismuth nitrate, hexadecyltrimethylammonium bromide and sodium tungstate is 1-3 mmol: 0.08-0.12 g: 0.8-1.2 mmol.
[0014] Bismuth nitrate and sodium tungstate may also be used in the form of hydrates thereof.
[0015] Furthermore, in step (2), the hydrothermal reaction is carried out at a temperature of 170-190° C. for 10-15 hours.
[0016] Furthermore, in step (3), the mass ratio of indium phosphide quantum dots to bismuth tungstate micro-flowers is 0.5-5:1.
[0017] Furthermore, in step (3), the reaction is heated at 170-190° C. for 10-15 h.
[0018] The present invention also provides an indium phosphide quantum dot-bismuth tungstate composite material prepared by the preparation method of the indium phosphide quantum dot-bismuth tungstate composite material.
[0019] The present invention also provides application of the indium phosphide quantum dot-bismuth tungstate composite material in photocatalytic production of hydrogen peroxide.
[0020] The present invention also provides application of the indium phosphide quantum dot-bismuth tungstate composite material in treating coking wastewater.
[0021] The present invention has the following beneficial effects:
[0022] 1. The InP / Bi2WO6 composite material of the present invention can photocatalytically generate H2O2 in pure water without using a sacrificial agent. InP / Bi2WO6 has a wide specific surface area, providing additional reaction sites for the photocatalytic process. For the InP / Bi2WO6 photocatalyst, the composite material exhibits an enhanced photocatalytic production of H2O2 yield, with a yield of up to 17.45mmol·g -1 ·h-1 , which are 90.8 times and 53.6 times of pure InP quantum dots and pure Bi2WO6 respectively.
[0023] 2. The H2O2 generated by the photocatalysis of InP / Bi2WO6 of the present invention can be used to remove chemical oxygen demand (COD) in actual coking wastewater, degrading the COD concentration of coking wastewater (about 150 mg / L) to below the national standard, paving the way for the application of photocatalytic systems in the fields of environment and energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD patterns of InP, Bi2WO6 and 3InP / Bi2WO6 prepared in Example 3;
[0025] Figure 2 The scanning electron microscope and transmission electron microscope observation results of InP, Bi2WO6 and 3InP / Bi2WO6 prepared in Example 3 are shown;
[0026] Figure 3 This is the test result of InP / Bi2WO6 photocatalytic H2O2 production under pure water conditions;
[0027] Figure 4 This is the test result of InP / Bi2WO6 photocatalytic H2O2 production under industrial water and tap water conditions;
[0028] Figure 5 This is the test result of InP / Bi2WO6 photocatalytic H2O2 production and degradation of COD in coking wastewater. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0030] Example 1
[0031] An indium phosphide quantum dot-bismuth tungstate composite material (0.5InP / Bi2WO6), the preparation method of which comprises the following steps:
[0032] (1) 0.25 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 120° C. under nitrogen protection, kept warm for 60 min, and then heated to 180° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 30 min to obtain indium phosphide quantum dots (InP);
[0033] (2) 2 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.1 g of hexadecyltrimethylammonium bromide and 1 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 180° C. for 12 h to obtain bismuth tungstate microflowers (Bi2WO6);
[0034] (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) in a mass ratio of 0.5:1 into deionized water and mixing them evenly, then heating at 180° C. for reaction for 12 h, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0035] Example 2
[0036] An indium phosphide quantum dot-bismuth tungstate composite material (1InP / Bi2WO6), the preparation method of which comprises the following steps:
[0037] (1) 0.25 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 120° C. under nitrogen protection, kept warm for 60 min, and then heated to 180° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 30 min to obtain indium phosphide quantum dots;
[0038] (2) 2 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.1 g of hexadecyltrimethylammonium bromide and 1 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 180° C. for 12 h to obtain bismuth tungstate microflowers;
[0039] (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) in a mass ratio of 1:1 into deionized water and mixing them evenly, then heating at 180° C. for reaction for 12 h, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0040] Example 3
[0041] An indium phosphide quantum dot-bismuth tungstate composite material (3InP / Bi2WO6), the preparation method of which comprises the following steps:
[0042] (1) 0.25 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 120° C. under nitrogen protection, kept warm for 60 min, and then heated to 180° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 30 min to obtain indium phosphide quantum dots;
[0043] (2) 2 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.1 g of hexadecyltrimethylammonium bromide and 1 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 180° C. for 12 h to obtain bismuth tungstate microflowers;
[0044] (3) The indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) are added into deionized water in a mass ratio of 3:1 and mixed evenly, and then heated at 180° C. for 12 h, cooled to room temperature, washed and dried to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0045] Example 4
[0046] An indium phosphide quantum dot-bismuth tungstate composite material (5InP / Bi2WO6), the preparation method of which comprises the following steps:
[0047] (1) 0.25 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 120° C. under nitrogen protection, kept warm for 60 min, and then heated to 180° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 30 min to obtain indium phosphide quantum dots;
[0048] (2) 2 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.1 g of hexadecyltrimethylammonium bromide and 1 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 180° C. for 12 h to obtain bismuth tungstate microflowers;
[0049] (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) in a mass ratio of 5:1 into deionized water and mixing them evenly, then heating at 180° C. for reaction for 12 h, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0050] Example 5
[0051] An indium phosphide quantum dot-bismuth tungstate composite material, the preparation method of which comprises the following steps:
[0052] (1) 0.2 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 110° C. under nitrogen protection, kept warm for 50 min, and then heated to 170° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 20 min to obtain indium phosphide quantum dots;
[0053] (2) 1 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.08 g of hexadecyltrimethylammonium bromide and 0.8 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 170° C. for 10 h to obtain bismuth tungstate microflowers;
[0054] (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) in a mass ratio of 0.5:1 into deionized water and mixing them evenly, then heating at 170° C. for reaction for 10 h, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0055] Example 6
[0056] An indium phosphide quantum dot-bismuth tungstate composite material (0.5InP / Bi2WO6), the preparation method of which comprises the following steps:
[0057] (1) 0.3 mmol of indium chloride was added to 10 mL of oleylamine and mixed, and then gradually heated to 130° C. under nitrogen protection, kept warm for 70 min, and then heated to 190° C., and then 0.5 mL of tri(diphenylphosphine) was added and reacted for 40 min to obtain indium phosphide quantum dots;
[0058] (2) 3 mmol of bismuth nitrate pentahydrate was dispersed in deionized water, 0.12 g of hexadecyltrimethylammonium bromide and 1.2 mmol of sodium tungstate dihydrate were added in sequence and stirred evenly, and then hydrothermally reacted at 190° C. for 15 h to obtain bismuth tungstate microflowers;
[0059] (3) The indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) are added into deionized water in a mass ratio of 5:1 and mixed evenly, and then heated at 190° C. for 15 h, cooled to room temperature, washed and dried to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
[0060] Test Example 1
[0061] (1) The phase structures of indium phosphide quantum dots (InP), bismuth tungstate microflowers (Bi2WO6) and indium phosphide quantum dots-bismuth tungstate composite materials (3InP / Bi2WO6) prepared in Sample Example 3 were characterized by XRD. The results are as follows: Figure 1 shown.
[0062] The diffraction peaks of InP at 26.3°, 30.4°, 43.6°, 51.6°, 54.1° and 63.4° can be attributed to the (111), (200), (220), (311), (222) and (400) crystal planes of InP. All diffraction peaks of the synthesized InP quantum dots can be well matched with the PDF#32-0452 card, without additional high crystallinity impurity peaks, proving the successful synthesis of pure phase InP. Similarly, the diffraction peaks of 28.31°, 32.90°, 47.16°, 55.89° and 58.61° are all attributed to the (131), (200), (202), (133) and (182) crystal planes of Bi2WO6. The peak positions are consistent with the Bi2WO6 PDF#39-0256 standard card. According to the XRD spectrum of InP / Bi2WO6 composite material, it was observed that both InP and Bi2WO6 had obvious peaks without any additional peaks, which confirmed that the composite material was successfully prepared.
[0063] (2) The morphologies of Bi2WO6, InP and 3InP / Bi2WO6 prepared in Example 3 were observed by scanning electron microscopy and transmission electron microscopy. Figure 2 As shown, ac is the SEM, TEM and HRTEM images of Bi2WO6, d is the SAED image of Bi2WO6, e is the HRTEM image of InP, f is the HRTEM image of 3InP / Bi2WO6 composite material, and Bi, W, O, In and P are the corresponding EDS element maps.
[0064] Depend on Figure 2 It can be seen that Bi2WO6 presents petal-like clusters composed of nanosheets with an average diameter of 1μm. Obviously, this structure has a large surface area containing many active sites. The TEM image of Bi2WO6 shows that the edges of Bi2WO6 are square laminar with a size of about 50-100nm, and the HRTEM image further shows its internal structure. The lattice spacing corresponding to the (200) plane of Bi2WO6 is 0.273nm. In addition, the well-dispersed bright spots in the Bi2WO6 SAED pattern indicate the presence of a highly ordered crystal structure in the sample. HRTEM characterization of InP showed that the prepared InP quantum dots were spherical nanoparticles (, with a lattice spacing of 0.33nm, which matched the (111) plane of InP. From the TEM image of the 3InP / Bi2WO6 composite, it can be observed that the translucent nanosheets are wrapped by many nanoparticles. In addition, lattice fringes with a lattice spacing of 0.273nm were observed, belonging to the (200) plane of Bi2WO6. Element mapping of 3InP / Bi2WO6 showed the presence of Bi, W, O, In and P, proving that the composite material was successfully prepared.
[0065] Test Example 2
[0066] (1) Under the irradiation of a xenon lamp (300 W, λ>420 nm), the photocatalytic performance of the indium phosphide quantum dot-bismuth tungstate composite material prepared in Examples 1-4 was tested in pure water (no sacrificial agent added, 20 mg of the composite material, 50 mL of H2O+O2). The results are as follows: Figure 3 The results show that the indium phosphide quantum dots-bismuth tungstate composite material of the present invention exhibits enhanced photocatalytic H2O2 yield, among which the maximum yield of 3InP / Bi2WO6 reaches 17.45mmol·g -1 ·h -1 , which are 90.8 times and 53.6 times of pure InP and Bi2WO6 respectively.
[0067] (2) The efficiency of InP / Bi2WO6 was also demonstrated in tap water and industrial wastewater. Figure 4 As shown in Figure 2, although the synthesis efficiency of H2O2 decreased in the complex system, the synthesis efficiency of the photocatalyst in industrial wastewater and tap water was 3.38 mmol·g -1 ·h -1 and 13.31mmol·g -1 ·h -1 .
[0068] (3) From the above experiments, it can be seen that InP / Bi2WO6 has great potential as an innovative and green method to produce H2O2 using H2O, O2 and light. In order to study the effect of photocatalytic generation of H2O2, the synthesized H2O2 was used to degrade the chemical oxygen demand (COD) in coking wastewater. The results are shown in Figure 2. Figure 5 As shown in the figure, after irradiation with simulated sunlight, the photodegradation efficiency of COD reached about 60%. The COD concentration increased from 150 mg·L -1 Reduced to 60 mg·L -1 , far lower than the emission standards of the coking industry.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an indium phosphide quantum dot-bismuth tungstate composite material, characterized in that: The following steps are involved: (1) adding an indium precursor to oleylamine and mixing, then gradually heating to 110-130° C. under nitrogen protection, keeping the temperature for a period of time, then heating to 170-190° C., and then adding tri(diphenylphosphine) to react to obtain indium phosphide quantum dots; (2) dispersing bismuth nitrate in deionized water, adding hexadecyltrimethylammonium bromide and sodium tungstate in sequence and stirring evenly, and then performing a hydrothermal reaction to obtain bismuth tungstate microflowers; (3) adding the indium phosphide quantum dots obtained in step (1) and the bismuth tungstate microflowers obtained in step (2) into deionized water and mixing them evenly, then heating for reaction, cooling to room temperature, washing and drying to obtain an indium phosphide quantum dot-bismuth tungstate composite material.
2. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (1), the indium precursor is indium chloride.
3. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (1), the molar volume ratio of the indium precursor, oleylamine and tri(diphenylphosphine) is 0.2-0.3 mmol:10 mL:0.5 mL.
4. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (1), the temperature is kept at 50-70 minutes and the reaction is carried out for 20-40 minutes.
5. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (2), the usage ratio of bismuth nitrate, hexadecyltrimethylammonium bromide and sodium tungstate is 1-3mmol:0.08-0.12g:0.8-1.2mmol.
6. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (3), the mass ratio of the indium phosphide quantum dots to the bismuth tungstate micro-flowers is 0.5-5:
1.
7. The method for preparing the indium phosphide quantum dot-bismuth tungstate composite material according to claim 1, characterized in that: In step (3), the reaction is heated at 170-190°C for 10-15h.
8. An indium phosphide quantum dot-bismuth tungstate composite material obtained by the preparation method of the indium phosphide quantum dot-bismuth tungstate composite material according to any one of claims 1 to 7.
9. Use of the indium phosphide quantum dot-bismuth tungstate composite material according to claim 8 in photocatalytic production of hydrogen peroxide.
10. Use of the indium phosphide quantum dot-bismuth tungstate composite material according to claim 8 in treating coking wastewater.
Citation Information
Patent Citations
Quantum dot composite material and preparation method thereof
CN109929549A
Catalyst modification method and photocatalyst
CN114345379A
Carbon nitride quantum dot / bismuth tungstate heterojunction, preparation method thereof and application of carbon nitride quantum dot / bismuth tungstate heterojunction in photocatalytic carbon dioxide reduction
CN117548096A
Preparation method of BiVO4 photocatalyst
CN118356929A
Method of manufacturing quantum dot
JP2023033157A